Managing Psoriatic Arthritis With Inflammatory Bowel Disease and/or Uveitis - Chia, Alfred Yu Ting; Ang, Gladys Wei Xin; Chan, Anita Sook Yee; Chan, Webber; Chong, Timothy Kit Yeong; Leung, Ying Ying (Frontiers in Medicine, 2021)
Psoriatic arthritis (PsA) is a chronic inflammatory disease that presents with psoriasis and peripheral and axial arthropathy. The heterogeneity of disease presentation leads to the term “psoriatic disease (PsD)” which is thought to better encompass the range of clinical manifestations. PsA is associated with several comorbidities such as cardiovascular diseases, metabolic syndrome and other extra-articular manifestations including uveitis, and inflammatory bowel disease (IBD). While novel therapeutics are being developed following advances in our understanding of the pathogenesis of the disease, the diverse combinations of PsA with its various comorbidities still pose a clinical challenge in managing patients with PsA. This article reviews our current understanding of the pathogenesis of PsA and how various pathways in the pathogenesis lead to the two comorbid extra-articular manifestations – uveitis and IBD. We also review current evidence of treatment strategies in managing patients with PsA with comorbidities of uveitis and/or IBD.